Exercise during transition from compensated left ventricular hypertrophy to heart failure in aortic stenosis rats - Reyes, David R. A. [UNESP]; Gomes, Mariana J. [UNESP]; Rosa, Camila M. [UNESP]; Pagan, Luana U. [UNESP]; Zanati, Silmeia G. [UNESP]; Damatto, Ricardo L. [UNESP]; Rodrigues, Eder A. [UNESP]; Carvalho, Robson F. [UNESP]; Fernandes, Ana A. H. [UNESP]; Martinez, Paula F.; Lima, Aline R. R. [UNESP]; Cezar, Marcelo D. M. [UNESP]; et al. (Wiley, 2019)
We evaluated the influence of aerobic exercise on cardiac remodelling during the transition from compensated left ventricular (LV) hypertrophy to clinical heart failure in aortic stenosis (AS) rats. Eighteen weeks after AS induction, rats were assigned into sedentary (AS) and exercised (AS-Ex) groups. Results were compared to Sham rats. Exercise was performed on treadmill for 8 weeks. Exercise improved functional capacity. Echocardiogram showed no differences between AS-Ex and AS groups. After exercise, fractional shortening and ejection fraction were lower in AS-Ex than Sham. Myocyte diameter and interstitial collagen fraction were higher in AS and AS-Ex than Sham; however, myocyte diameter was higher in AS-Ex than AS. Myocardial oxidative stress, evaluated by lipid hydroperoxide concentration, was higher in AS than Sham and was normalized by exercise. Gene expression of the NADPH oxidase subunits NOX2 and NOX4, which participate in ROS generation, did not differ between groups. Activity of the antioxidant enzyme superoxide dismutase was lower in AS and AS-Ex than Sham and glutathione peroxidase was lower in AS-Ex than Sham. Total and reduced myocardial glutathione, which is involved in cellular defence against oxidative stress, was lower in AS than Sham and total glutathione was higher in AS-Ex than AS. The MAPK JNK was higher in AS-Ex than Sham and AS groups. Phosphorylated P38 was lower in AS-Ex than AS. Despite improving functional capacity, aerobic exercise does not change LV function in AS rats. Exercise restores myocardial glutathione, reduces oxidative stress, impairs JNK signalling and further induces myocyte hypertrophy.
Keywords: cardiac remodelling; echocardiogram; MAPK; oxidative stress; physical training; rat